Anti-Thermal Quenching in Ndiii Molecular Near-Infrared Thermometers Operating at Physiological Temperatures - Aravena-Ponce, D; Aravena-Ponce, D (Nature Research, 2025)
Examples of molecular complexes acting as thermometers operating at room temperature in near infrared region are scarce, therefore this work showcases the anti-thermal quenching effect on neodymium(III) molecular thermometers working in biological windows within the physiological temperature range. A mononuclear complex, [Nd(L)(NO3)3] (1Nd), where L is a macrocyclic ligand, was synthesized and used as a precursor to develop two novel species: a dinuclear, [(Nd(L)(NO3))2(µ-BDC)](NO3)2·H2O (2Nd), linked by 1,4-benzenedicarboxylate (BDC), and a hexameric, [(Nd(L))(µ-BTC)(H2O)]6·35H2O (6Nd), linked with 1,3,5-benzenetricarboxylate (BTC). Thermometric properties were studied in the physiological temperature range (292-332 K), utilizing 804 nm laser excitation (first biological window) and monitoring emissions in the second biological window (908, 1065, and 1340 nm) associated with the 4F3/2 → 4I9/2, 4I11/2, 4I13/2 transitions, respectively. Among the complexes, the hexamer 6Nd exhibited exceptional performance, with Sr of 2.4%K−1 at 293 K, when luminescence intensity ratio (LIR) of two Stark components of the 4F3/2 → 4I11/2 emission was used, positioning it as a high-performance NdIII-based thermometer. All complexes displayed anti-thermal quenching behavior, surpassing the current molecular-based thermometers in the near-infrared region. Theoretical calculations using complete active space self consistent field (CASSCF) and Boltzmann population models between Kramers doublets of the 4F3/2 level were performed to rationalize the anti-thermal behavior. (Figure presented.) © The Author(s) 2025.